Intercultural Communication and Purchase Behaviour Towards Japanese Electric Vehicles Among the Chinese Young Generation - Rui Sun; Yi-Fang Yuan; Lei Wang (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Previous studies have mainly investigated the influence of intercultural communication on consumer purchase behaviour based on the theory of planned behaviour within a single cultural setting. This study aims to investigate how intercultural communication influences the attitudes, subjective norm, perceived behavioural control, and willingness to buy Japanese electric vehicles among the Chinese young generation. A purposive sampling method was employed to select students from various academic disciplines at six bachelor’s universities in Xuzhou city, China. A survey method was used to collect data, and a total of 398 university students were included in the analysis. The results showed that attitude, subjective norm, and perceived behavioural control positively influenced willingness to buy. Intercultural communication positively influenced attitude, subjective norm, perceived behavioural control, and willingness to buy, respectively. The current study extends the existing knowledge on how intercultural communication influenced the Chinese young generation’s willingness to buy Japanese electric vehicles and benefited the Japanese electric vehicle industry and key stakeholders in marketing.